Renovating HR through Technology: A new organisational perspective - Sharma, Avnish; Panicker, Aneesya (International Journal of Psychosocial Rehabilitation, 2020)
Managing human resources is one of the most essential functions of an organization. Without managing human resources, no organization can think of its success and survival in the face of fierce competition. In the current situation, technology is rapidly changing and adopting new technology solutions have become a major concern for today’s organizations to make their business more efficient and competitive. Technology can help organizations to better respond to growing expectations of internal and external organizational partners, improve the quality of work performed, and make more efficient use of available resources, i.e., time, money and people. In the current business context, technology has reinvented the way business operates, the day-to-day business processes and most importantly, the manpower processes and related practices. In fact, HR technology is increasingly being used to develop workplace solutions for HR and make profitable HR decisions. This is a conceptual paper focusing on the role and importance of technology in strategically managing HR work. This study includes understanding the notion and evolution of HR technology, concept of human resource information system(HRIS), consequences of executing HR technology, few popular software details generally practiced and used in organisations and also the case of popular business organisations which believes in using the technology in managing manpower related processes to earn financial and nonfinancial benefits.